Insights into sugar metabolism during bilberry (Vaccinium myrtillus L.) fruit development. Issue 2 (14th March 2022) - Samkumar, Amos; Karppinen, Katja; Dhakal, Binita; Martinussen, Inger; Jaakola, Laura
Abstract: Bilberry fruit is regarded as one of the best natural sources of anthocyanins and is widely explored for its health‐beneficial compounds. Besides anthocyanins, one of the major attributes that determine the berry quality is the accumulation of sugars that provide sweetness and flavor to ripening fruit. In this study, we have identified 25 sugar metabolism‐related genes in bilberry, including invertases (INVs), hexokinases (HKs), fructokinases (FKs), sucrose synthases (SSs), sucrose phosphate synthases (SPSs), and sucrose phosphate phosphatases (SPPs). The results indicate that isoforms of the identified genes are expressed differentially during berry development, suggesting specialized functions. The highest sugar content was found in ripe berries, with fructose and glucose dominating accompanied by low sucrose amount. The related enzyme activities during berry development and ripening were further analyzed to understand the molecular mechanism of sugar accumulation. The activity of INVs in the cell wall and vacuole increased toward ripe berries. Amylase activity involved in starch metabolism was not detected in unripe berries but was found in ripe berries. Sucrose resynthesizing SS enzyme activity was detected upon early ripening and had the highest activity in ripe berries. Interestingly, our transcriptome data showed that supplemental irradiation with red and blue light triggered upregulation of several sugar metabolism‐related genes, including α‐ and β‐amylases. Also, differential expression patterns in responses to red and blue light were found across sucrose, galactose, and sugar‐alcohol metabolism. Our enzymological and transcriptional data provide new understanding of the bilberry fruit sugar metabolism having major effect on fruit quality.